Longitudinal Impacts of Home Computer Use in Early Years on Children’s Social and Behavioral Development - Ebrahim Talaee (International Electronic Journal of Elementary Education, 2019)
This study presents a pattern for Home Computer Use (HCU) and its relation to children’s social and behavioural development during primary education. This study answers whether and how HCU (either educational or recreational) during primary school is related to children’s social/behavioural development such as self-regulation, anti-social behaviour and pro-social behaviour. To do so, information about types and fre-quency of HCU from nearly 2000 children were analysed using hierarchical linear regression and path analysis on children ranging from 3 to 11 years old. Hierarchical linear regression was applied to study the main effects (i.e. direct effects) and the path analysis was used to investigate mediating (i.e. indirect effects) of HCU on children outcomes. The results showed that the use of HCU for playing games has a linear and nega-tive association with children’s Pro-social behaviour as reported by class teachers in Year 6, while the effects of other background characteristics were partialled out. Two other social/behavioural outcomes – anti-social behaviour and self-regulation – were not associated with children’s HCU over and beyond what can be predicted based on children’s prior social/behavioural profile and their demographic background character-istics. The theoretical and practical implications of these results are discussed.